Attitude control of quadrotors based on fractional sliding modes: theory and experiments. Issue 7 (1st April 2016) - Izaguirre‐Espinosa, Carlos; Muñoz‐Vázquez, Aldo Jonathan; Sánchez‐Orta, Anand; Parra‐Vega, Vicente; Castillo, Pedro
Abstract : Light weight quadrotors are highly manoeuvrable autonomous aerial robots (UAV) that outperform most UAVs; however, quadrotors are prone to a wide class of aerodynamic disturbances, vibrations, and uncertainties that demand not only robust but fast attitude control structures. These arguments are compelling enough to motivate the design of a novel fractional‐order control scheme that enforces finite‐time convergence of the sliding manifold to guarantee local exponential tracking. The controller does not exhibit chattering and does not require the knowledge of the dynamic model. The stability analysis is based on a proposed resetting memory principle to deal with memory effects of the differintegral operator, which allows the controller to tackle also robustness against continuous disturbances that are not necessarily differentiable in the conventional sense such as some aerodynamic phenomena. Experimental evidence is presented and discussed to expose the enforcement of the sliding manifold based on a fractional‐order reaching phase that demonstrates the feasibility of the proposed control scheme.